MODELING OF BEHAVIORAL ACTIVITY OF AIR NAVIGATION SYSTEM'S HUMAN-OPERATOR IN FLIGHT EMERGENCIES - Kharchenko, Volodymyr; Shmelova, Tetyana; Sikirda, Yuliya (Proceedings of National Aviation University, 2012)
The Air Navigation System is presented as a complex socio-technical system. The influence on decision-making by Air Navigation System's human-operator of the professional factors as well as the factors of non-professional nature has been defined. Logic determined and stochastic models of decision-making by the Air Navigation System's human-operator in flight emergencies have been developed. The scenarios of developing a flight situation in case of selecting either the positive or negative pole in accordance with the reflexive theory have been obtained. The informational support system of the operator in the unusual situations on the basis of Neural Network model of evaluating the efficiency of the potential alternative of flight completion has been built.